O Grupo Escolar da Fazenda Amália: contribuições para a história da instituição entre 1942 e 1966 - Costa, Islan Reinaldo da (2007)
The present research is intended to rebuild the history of Fazenda Amália school, located in the city of Santa Rosa do Viterbo area of Ribeirão Preto, the countryside of São Paulo State from 1942 to 1966, when a general strike happened which led to its decline. It is the study of a school institution that, despite of being public, was located inside a private property (farm): Fazenda Amália, that belonged to Matarazzo family and constituted one of the most important rural properties of the countryside in São Paulo regarding the culture of sugarcane, besides its inside sugar factory. Most of workers lived in the farm and, considering the great number of school aged children, Fazenda Amália School was created in 1942, which gathered the existent schools in the property. This study is based on the exam of the still available materials of the institution (Meeting Minutes, Students Books of Registrations, Diaries, Maps of the school movement; Inventory of possessions, Balance sheets, Books of Setlement, Registration Book; among others) and the accomplishment of interviews with 4 former teachers and principals. Through the analysis of that material, it was possible In this first version of the history of Fazenda Amália School to reconstitute some facets of the history of the institution, among them: the process of installation of the school and its expansion during the studied period, the characteristics of the faculty and administrative group and the students' profile concerning the origin, age group and school performance